2016
DOI: 10.3389/fmicb.2016.01876
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus thermophilus APC151 Strain Is Suitable for the Manufacture of Naturally GABA-Enriched Bioactive Yogurt

Abstract: Consumer interest in health-promoting food products is a major driving force for the increasing global demand of functional (probiotic) dairy foods. Yogurt is considered the ideal medium for delivery of beneficial functional ingredients. Gamma-amino-butyric acid has potential as a bioactive ingredient in functional foods due to its health-promoting properties as an anti-stress, anti-hypertensive, and anti-diabetic agent. Here, we report the use of a novel Streptococcus thermophilus strain, isolated from the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 46 publications
(54 reference statements)
1
44
0
Order By: Relevance
“…Consumption of food products high in galactose is harmful to individuals with galactosemia. Linares et al (2016) used S. thermophilus APC151 to produce yogurt that contains γ-aminobutyric acid (GABA) and that has comparable properties of a reference yogurt. γ-Aminobutyric acid promotes health by its anti-stress, anti-hypertensive, and anti-diabetic properties.…”
Section: Yogurt Cultures and Added Probioticsmentioning
confidence: 99%
“…Consumption of food products high in galactose is harmful to individuals with galactosemia. Linares et al (2016) used S. thermophilus APC151 to produce yogurt that contains γ-aminobutyric acid (GABA) and that has comparable properties of a reference yogurt. γ-Aminobutyric acid promotes health by its anti-stress, anti-hypertensive, and anti-diabetic properties.…”
Section: Yogurt Cultures and Added Probioticsmentioning
confidence: 99%
“…(D) Intracellular pH (pH in ) value of CS9 cells under different growth conditions. other S. thermophilus GABA-producing strains, such as Y2 (7984.75 ± 293.33 mg/l), APC151 (2 mg/ml), and ST110 (655 µM) (Yang et al, 2008;Somkuti et al, 2012;Linares et al, 2016). Therefore, the GABA-producing S. thermophilus CS9 could be a new potential starter used in the production of functional foods rich in GABA by means of optimization of fermentation conditions.…”
Section: The Growth Curves and Stress Resistance Of Strainsmentioning
confidence: 99%
“…The latter gene along with glutamate decarboxylase gene (gadB) are responsible for gamma-aminobutyric acid (GABA) production. It was recently demonstrated that strain APC151 is a high-yield GABA producer (Linares et al, 2016). In strain KLDS 3.1003 a unique histidine/histamine antiporter has been also identified (hdcP) ( Supplementary Table S5B).…”
Section: Proteolytic Systemmentioning
confidence: 99%